Pengaruh Persepsi Kualitas, Persepsi Nilai dan Kenyamanan Terhadap Minat Beli Street Food di Tangerang - Tri Kris Meidy; Regina Deka Sofia (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Potential street food buyers can be interested in buying a product based on perceived quality, perceived value and convenience. So that the attitude of potential buyers to buy the product arises. This study aims to determine the effect of perceived value, perceived quality and convenience and attitudes on the interest in buying street food. The research plan is explanatory research using a sample of 130 respondents, namely potential street food buyers. This study is purposive sampling. Multiple linear regression analysis is assisted by the IBM SPSS statistic 25 application and model and hypothesis analysis with Smart SEM PLS. The results of data processing show that perceived quality has a positive effect on attitudes. Perception of value has a positive effect on attitudes. Convenience does not have a positive effect on attitudes. Attitude has a positive effect on the interest in buying street food in Tangerang.